2011
DOI: 10.1111/j.1540-8175.2011.01389.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Position Changes on Myocardial Velocity in Healthy Subjects Evaluated by Tissue Doppler Echocardiography*

Abstract: Tricuspid anulus myocardial tissue velocities may be significantly influenced by changing of position in healthy subjects. Effect of position changes should be considered in the assessment of these velocities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A large number of studies have investigated the influence of age, gender, postural change, lower body negative pressure, exercise, pharmacological manoeuvres, etc. on tissue Doppler parameters, and several reference values have been proposed (Wilkenshoff et al, 1998;Alam et al, 1999;Kukulski et al, 2000;Nikitin et al, 2003;Am a et al, 2004;Pel a et al, 2004;Lindqvist et al, 2005;Innelli et al, 2008;Pirat et al, 2008;Chahal et al, 2010;Uz et al, 2011). Food intake is known to significantly alter the hemodynamics of the heart (Fagan et al, 1986;Ishimine et al, 1994;Gilligan et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have investigated the influence of age, gender, postural change, lower body negative pressure, exercise, pharmacological manoeuvres, etc. on tissue Doppler parameters, and several reference values have been proposed (Wilkenshoff et al, 1998;Alam et al, 1999;Kukulski et al, 2000;Nikitin et al, 2003;Am a et al, 2004;Pel a et al, 2004;Lindqvist et al, 2005;Innelli et al, 2008;Pirat et al, 2008;Chahal et al, 2010;Uz et al, 2011). Food intake is known to significantly alter the hemodynamics of the heart (Fagan et al, 1986;Ishimine et al, 1994;Gilligan et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Recently, several studies reported the feasibility of TDI for assessing fetal cardiac function, demonstrating ventricular myocardial velocity changes in relation to advancing gestational age. [1][2][3][4][5][6][7][8] Recently, several studies reported the feasibility of TDI for assessing fetal cardiac function, demonstrating ventricular myocardial velocity changes in relation to advancing gestational age.…”
mentioning
confidence: 99%
“…Tissue Doppler imaging (TDI) represents a new development of the Doppler technique, allowing direct measurements of contraction and relaxation velocities directly from the myocardium. [1][2][3][4][5][6][7][8] Recently, several studies reported the feasibility of TDI for assessing fetal cardiac function, demonstrating ventricular myocardial velocity changes in relation to advancing gestational age. [9][10][11][12] TDI includes several new techniques, such as quantitative tissue velocity imaging (QTVI) and strain and strain rate imaging.…”
mentioning
confidence: 99%